1986
DOI: 10.1097/00006842-198605000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of interleukin-1 and immune functions to sleep in humans.

Abstract: Serial sampling of peripheral blood from six healthy adult male volunteers was performed during daytime waking and nighttime sleeping. In addition, sleep physiology was assessed in all subjects (Ss) and sleep stages scored blind by standard criteria. Samples of plasma were analyzed for cortisol (Co) levels, functional interleukin-1 (IL-1), and interleukin-2 (IL-2) activity. Peripheral blood monocytes (PBM) were assayed to evaluate natural killer (NK) activity and mitogen responsiveness. Dramatic increase in IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(82 citation statements)
references
References 0 publications
5
71
0
4
Order By: Relevance
“…29,36,[73][74][75] In healthy humans, the levels of IL-1b in blood plasma are highest at the onset of sleep. 16,76 This and other evidence, including circadian control of the production of somnogenic cytokines, indicates their involvement in physiological sleep regulation. Activated processing and release of cytokines by microglia (brain phagocytes) is caused in part by rising levels of extracellular ATP during wakefulness.…”
Section: Relationship Of Protein Fragments To Other Somnogensmentioning
confidence: 86%
See 1 more Smart Citation
“…29,36,[73][74][75] In healthy humans, the levels of IL-1b in blood plasma are highest at the onset of sleep. 16,76 This and other evidence, including circadian control of the production of somnogenic cytokines, indicates their involvement in physiological sleep regulation. Activated processing and release of cytokines by microglia (brain phagocytes) is caused in part by rising levels of extracellular ATP during wakefulness.…”
Section: Relationship Of Protein Fragments To Other Somnogensmentioning
confidence: 86%
“…56,65,66 As described below, these and other inflammatory cytokines can act as somnogens, indicating a major but incompletely understood connection between the immune system and sleep. 4,16,29,31,36,[67][68][69][70][71][72][73][74][75][76][77][78][79] Another potent endogenous somnogen is the PGD 2 prostaglandin, which preferentially induces NREM sleep. 11,28,80,81 The somnogenic activity of PGD 2 is mediated at least in part by the ability of brain-produced PGD 2 to increase the concentration of extracellular adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to IL-1, there are diurnal rhythms to IL-1 message and protein that are in phase with major sleep periods (Moldofsky et al, 1986;Lue et al, 1987;Taishi et al, 1998). Administration of IL-1 into laboratory animals increases the amount of time spent in NREM sleep, whereas antagonizing the IL-1 system with receptor antagonists, soluble receptors or antibodies reduces NREM sleep [reviewed (Krueger et al, 2001; Opp and Toth, 2003;Opp, 2005)].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that NK cells defend against tumor cell growth and viral infections in human cellular immune systems, and that NK cell functions are variously influenced by workload [15][16][17] , mental health 20-22, 24, 25) , and life style [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) .…”
Section: Discussionmentioning
confidence: 99%